Antibacterial TPV (thermoplastic vulcanizate) material for automobiles and preparation method of antibacterial TPV material
By combining chitosan/nano zinc oxide/porous silica composite material with carbon black-wollastonite filler, the problems of existing TPV materials in terms of antibacterial performance, heat resistance, cost and dispersibility are solved, and a highly efficient antibacterial TPV material suitable for automobiles is prepared.
Patent Information
- Application Number
- CN202411532845.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-30
AI Technical Summary
Existing automotive TPV materials have shortcomings in terms of antibacterial properties, heat resistance, cost, safety, and dispersibility. In particular, nano-ZnO tends to agglomerate in TPV materials, resulting in poor antibacterial effects.
A chitosan/nano zinc oxide/porous silica composite material was used as an antibacterial agent. By uniformly compositing nano ZnO on a porous SiO2 framework and combining the synergistic effect of chitosan, the agglomeration of nano ZnO was avoided. Carbon black and wollastonite were used as fillers to prepare an antibacterial TPV material for automobiles.
We have developed a TPV material for automobiles that features excellent antibacterial properties, good heat resistance, low cost, and good dispersibility. It also possesses good mechanical properties and antibacterial effects, making it suitable for various parts of automobiles.
Smart Images

Figure BDA0005110829270000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an antibacterial TPV material for automobiles and a preparation method thereof. Background Art
[0002] With the development of science and technology and the gradual improvement of the quality of life, people pay more and more attention to their own health and safety, and pay more attention to their own health protection. Therefore, with the rapid development of the automotive industry and the improvement of consumers' health requirements, the development of automotive materials with high-efficiency antibacterial properties has become an industry trend.
[0003] Antimicrobial agents are mainly divided into three categories. The first category is natural antimicrobial agents such as chitosan, peptides and essential oils extracted from animals and plants; the second category is organic antimicrobial agents such as quaternary ammonium salts, guanidines and halogenated phenols; the third category is inorganic antimicrobial agents such as metals such as Ag, Cu and Hg, and non-metals and metal oxides such as TiO2, ZnO and CeO2. Among them, natural antimicrobial agents have good biocompatibility, fast degradation, and almost no pollution, but their heat resistance and stability are poor; organic antimicrobial agents have strong bactericidal power and a variety of types, but they have disadvantages such as high toxicity, microbial resistance, and poor heat resistance; while inorganic antimicrobial agents have the advantages of broad-spectrum antimicrobial, high temperature resistance, and strong durability.
[0004] Patent CN107245187A uses a mixture of polyhexamethyleneguanidine hydrochloride and nano-silver as an antibacterial agent to prepare an antibacterial TPV composite material, which has a high cost and silver ions can cause certain harm to the environment and human body; Patent CN115536948A uses nano-ZnO as an antibacterial agent to prepare an antibacterial TPV material. Nano-ZnO is small in size, poor in dispersibility, and prone to agglomeration. Agglomeration may occur during the preparation of the TPV material, resulting in uneven distribution in the material and unclear antibacterial effect.
[0005] Therefore, in the preparation of TPV materials for automobiles, there is an urgent need for an antibacterial agent with excellent antibacterial properties, good heat resistance, low cost, safety, no pollution, good dispersibility and no agglomeration during the material processing. Summary of the invention
[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide an antibacterial TPV material for automobiles.
[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: an antibacterial TPV material for automobiles, comprising the following components in parts by weight:
[0010] EPDM rubber: 100 parts;
[0011] Polypropylene: 50-70 parts;
[0012] Filler: 40-60 parts;
[0013] Filler oil: 60-80 parts;
[0014] Antibacterial agent: 1 to 3 parts;
[0015] Vulcanizing agent: 2-4 parts;
[0016] Vulcanizing agent: 1-2 parts;
[0017] Antioxidant: 0.5-1 part;
[0018] Anti-ultraviolet agent: 0.5-1 part;
[0019] Wherein, the antibacterial agent is a chitosan / nano zinc oxide / porous silicon oxide composite material;
[0020] The filler is a composition of carbon black and wollastonite.
[0021] As a preferred embodiment of the antibacterial TPV material for automobiles of the present invention, the preparation method of the chitosan / nano zinc oxide / porous silicon oxide composite material comprises:
[0022] Weigh chitosan, add it to acetic acid aqueous solution to dissolve, then add zinc acetate dihydrate, stir and react at 70°C after dissolution, gradually add NaOH solution to adjust the pH of the reaction solution to 9-10 to promote ZnO precipitation, and continue to stir the reaction solution to ensure that nano ZnO particles are fully formed;
[0023] The mixture was allowed to stand for precipitation, filtered, and repeatedly washed with ethanol and deionized water until no residual liquid was left, and dried to obtain a chitosan-modified nano zinc oxide CS / ZnO composite material;
[0024] Weigh porous SiO2 and prepare it into a 5% SiO2 suspension with deionized water;
[0025] The CS / ZnO composite material was added to the prepared SiO2 suspension, stirred, allowed to settle, filtered, washed, dried at 70°C for 12 hours, and then dried at 150°C for 2 hours to obtain a chitosan / nano zinc oxide / porous silica composite material.
[0026] As a preferred embodiment of the antibacterial TPV material for automobiles of the present invention, the mass ratio of chitosan to zinc acetate dihydrate is 1:1, and the mass concentration of the acetic acid aqueous solution is 1%.
[0027] As a preferred embodiment of the antibacterial TPV material for automobiles of the present invention, the mass ratio of chitosan to porous SiO2 is 44:6, and the pore size of the porous SiO2 is 30-50 nm.
[0028] As a preferred embodiment of the antibacterial TPV material for automobiles of the present invention, the mass ratio of the carbon black to wollastonite is 1:2.
[0029] As a preferred embodiment of the antibacterial TPV material for automobiles of the present invention, the third monomer in the EPDM rubber is ethylidene norbornene, the third monomer accounts for 4.0-6.0%, and the Mooney viscosity is 60-70; the polypropylene is homopolymer polypropylene, and the melt flow rate is 2.5-3.5 g / 10 min.
[0030] As a preferred embodiment of the antibacterial TPV material for automobiles of the present invention, the vulcanizing agent is a peroxide vulcanizing agent, including dicumyl peroxide DCP;
[0031] The co-vulcanizing agent is one or a combination of triallyl cyanurate TAC and triallyl isocyanurate TAIC;
[0032] The filler oil is paraffin oil.
[0033] As a preferred embodiment of the antibacterial TPV material for automobiles of the present invention, the antioxidant is a hindered phenol antioxidant, including one or more combinations of antioxidant 1076, antioxidant 264, and antioxidant 1010;
[0034] The anti-ultraviolet agent is a dihydroxybenzophenone, including 2-hydroxy-4-methoxy-benzophenone.
[0035] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing an antibacterial TPV material for automobiles, comprising:
[0036] Add EPDM rubber, polypropylene, filler, filling oil, antibacterial agent, antioxidant and anti-ultraviolet agent into a mixer and mix them evenly, then send them into a twin-screw extruder for extrusion and granulation to obtain semi-finished particles;
[0037] The obtained semi-finished product particles are mixed evenly with a vulcanizing agent and a vulcanizing co-agent, and sent to a twin-screw extruder for mixing and vulcanization, extruded, cooled and shaped to obtain an antibacterial TPV material for automobiles.
[0038] As a preferred embodiment of the method for preparing the antibacterial TPV material for automobiles of the present invention, the operating temperature of the twin-screw extruder for preparing the semi-finished particles is 150-180°C, and the screw speed is 250-300rpm;
[0039] The mixture is sent to a twin-screw extruder for mixing and vulcanization, wherein the operating temperature of the twin-screw extruder is 160-190° C. and the screw speed is 200-250 rpm.
[0040] Beneficial effects of the present invention:
[0041] (1) The present invention prepares a chitosan / nano zinc oxide / porous silica (CS / ZnO / SiO2) composite material as an antibacterial agent, so that nano ZnO is evenly compounded on the skeleton of porous SiO2, effectively avoiding the problem of agglomeration between nano ZnO particles leading to a decrease in antibacterial performance; in addition, the antibacterial performance of nano ZnO is mainly based on the strong oxidizing free radicals generated by photocatalysis, which can destroy important biological molecules in bacterial cells. The antibacterial performance of nano ZnO is weakened under lightless conditions. After being compounded with CS, the disadvantage of the decreased antibacterial performance of TPV materials in a lightless environment can be compensated. The composite of nano ZnO and CS can also play a synergistic role, thereby increasing the antibacterial performance of the antibacterial material as a whole.
[0042] (2) The present invention uses CS / ZnO / SiO2 as an antibacterial agent, and the prepared TPV material has good wear resistance, compression deformation resistance, aging resistance and other properties. It can be widely used in various TPV material-using parts of automobiles and has good antibacterial effect. DETAILED DESCRIPTION
[0043] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0044] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0045] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0046] In the embodiment of the present invention:
[0047] EPDM rubber comes from Shanghai Sinopec Mitsui Elastomer Co., Ltd., with an ethylene content of >60%, ethylidene norbornene as the third monomer, accounting for 4.0-6.0%, and a Mooney viscosity of 60-70;
[0048] Polypropylene was from Changzhou Haihong Plastic Technology Co., Ltd., with a melt flow rate of 2.5-3.5 g / 10 min;
[0049] The filler oil was from Shandong Jinli Chemical Co., Ltd.;
[0050] Chitosan was from Jiangsu Dongju Biotechnology Co., Ltd.;
[0051] Porous SiO2 comes from Hangzhou Jikang New Materials Co., Ltd., and the particle size is 30-40nm.
[0052] Example 1
[0053] This embodiment is a method for preparing a chitosan / nano zinc oxide / porous silica (CS / ZnO / SiO2) composite material, the main steps are:
[0054] (1) Weigh 44 kg of chitosan, add it to 1000 kg of 1% acetic acid aqueous solution to dissolve it, then add 44 kg of zinc acetate dihydrate, stir and react at 70° C. after dissolution, gradually add 1 mol / L NaOH solution to adjust the pH of the reaction solution to 10 to promote ZnO precipitation, and continue to stir the reaction solution for 4 hours to ensure that ZnO particles are fully formed;
[0055] The precipitate was allowed to stand for 24 hours, filtered, and repeatedly washed with ethanol and deionized water until no residual liquid was left. The precipitate was dried at 70°C for 12 hours to obtain a chitosan-modified nano-zinc oxide (CS / ZnO) composite material.
[0056] (2) Weigh 6 kg of porous SiO2 material with a pore size of 30 to 50 nm and prepare it into a 5% SiO2 suspension with deionized water;
[0057] (3) The CS / ZnO composite material was added to the SiO2 suspension obtained in (2), stirred for 12 h, allowed to settle for 24 h, filtered, washed, dried at 70°C for 12 h, and then dried at 150°C for 2 h to obtain a chitosan / nano zinc oxide / porous silica (CS / ZnO / SiO2) composite material.
[0058] Example 2
[0059] This embodiment provides a method for preparing an antibacterial TPV material for automobiles, comprising the following components in parts by weight:
[0060] EPDM rubber: 100 parts;
[0061] Polypropylene: 60 parts;
[0062] Filler: carbon black:wollastonite = 1:2 composition, 50 parts;
[0063] Filler oil: paraffin oil, 70 parts;
[0064] Antimicrobial agent: 2 parts;
[0065] Curing agent: dicumyl peroxide DCP, 3 parts;
[0066] Vulcanizing agent: 1.5 parts;
[0067] Antioxidant: 0.8 parts;
[0068] Anti-ultraviolet agent: 2-hydroxy-4-methoxy-benzophenone, 0.8 parts.
[0069] Among them, the antibacterial agent is the CS / ZnO / SiO2 composite material prepared in Example 1, the vulcanizing agent is triallyl cyanurate (TAC), and the antioxidant is antioxidant 1010.
[0070] The preparation process is as follows:
[0071] S1: adding EPDM rubber, polypropylene, filler, filling oil, antibacterial agent, antioxidant and anti-ultraviolet agent into a mixer and mixing them evenly, and then feeding them into a twin-screw extruder for extrusion granulation to obtain semi-finished particles;
[0072] S2: The semi-finished product particles are mixed evenly with the vulcanizing agent and the co-vulcanizing agent, and then sent to a twin-screw extruder for mixing and vulcanization, extruded, cooled and shaped to obtain the antibacterial TPV material for automobiles.
[0073] Wherein, in step S1, the operating temperatures of each zone of the twin-screw extruder are: 150°C, 160°C, 170°C, 175°C, 180°C, 180°C, 170°C, and the screw speed is 280 rpm;
[0074] In step S2, the operating temperatures of each zone of the twin-screw extruder are 160° C., 170° C., 180° C., 185° C., 190° C., 190° C., and 180° C., and the screw speed is 220 rpm.
[0075] Example 3
[0076] An antibacterial TPV material for automobiles and a preparation method thereof, comprising the following components in parts by weight:
[0077] EPDM rubber: 100 parts;
[0078] Polypropylene: 70 parts;
[0079] Filler: carbon black:wollastonite = 1:2 composition, 60 parts;
[0080] Filler oil: paraffin oil, 80 parts;
[0081] Antimicrobial agent: 3 parts;
[0082] Curing agent: dicumyl peroxide DCP, 4 parts;
[0083] Vulcanizing agent: 2 parts;
[0084] Antioxidant: 1 part;
[0085] Anti-ultraviolet agent: 2-hydroxy-4-methoxy-benzophenone, 1 part.
[0086] The antibacterial agent is the CS / ZnO / SiO2 composite material prepared in Example 1, the vulcanizing agent is triallyl cyanurate (TAC), and the antioxidant is antioxidant 1010.
[0087] The preparation process is as follows:
[0088] S1: adding EPDM rubber, polypropylene, filler, filling oil, antibacterial agent, antioxidant and anti-ultraviolet agent into a mixer and mixing them evenly, and then feeding them into a twin-screw extruder for extrusion granulation to obtain semi-finished particles;
[0089] S2: The semi-finished product particles are mixed evenly with the vulcanizing agent and the co-vulcanizing agent, and then sent to a twin-screw extruder for mixing and vulcanization, extruded, cooled and shaped to obtain the antibacterial TPV material for automobiles.
[0090] Wherein, in step S1, the operating temperatures of each zone of the twin-screw extruder are: 150°C, 160°C, 170°C, 175°C, 180°C, 180°C, 170°C, and the screw speed is 300rpm;
[0091] In step S2, the operating temperatures of each zone of the twin-screw extruder are 160° C., 170° C., 180° C., 185° C., 190° C., 190° C., and 180° C., and the screw speed is 250 rpm.
[0092] Example 4
[0093] An antibacterial TPV material for automobiles and a preparation method thereof, comprising the following components in parts by weight:
[0094] EPDM rubber: 100 parts;
[0095] Polypropylene: 50 parts;
[0096] Filler: carbon black:wollastonite = 1:2 composition, 40 parts;
[0097] Filler oil: paraffin oil, 60 parts;
[0098] Antimicrobial agent: 1 part;
[0099] Curing agent: dicumyl peroxide DCP, 2 parts;
[0100] Vulcanizing agent: 1 part;
[0101] Antioxidant: 0.5 parts;
[0102] Anti-ultraviolet agent: 2-hydroxy-4-methoxy-benzophenone, 0.5 parts.
[0103] The antibacterial agent is the CS / ZnO / SiO2 composite material prepared in Example 1, the vulcanizing agent is triallyl isocyanurate (TAIC), and the antioxidant is antioxidant 1010.
[0104] The preparation process is as follows:
[0105] S1: adding EPDM rubber, polypropylene, filler, filling oil, antibacterial agent, antioxidant and anti-ultraviolet agent into a mixer and mixing them evenly, and then feeding them into a twin-screw extruder for extrusion granulation to obtain semi-finished particles;
[0106] S2: The semi-finished product particles are mixed evenly with the vulcanizing agent and the co-vulcanizing agent, and then sent to a twin-screw extruder for mixing and vulcanization, extruded, cooled and shaped to obtain the antibacterial TPV material for automobiles.
[0107] Wherein, in step S1, the operating temperatures of each zone of the twin-screw extruder are: 150°C, 160°C, 170°C, 175°C, 180°C, 180°C, 170°C, and the screw speed is 250rpm;
[0108] In step S2, the operating temperatures of each zone of the twin-screw extruder are 160° C., 170° C., 180° C., 185° C., 190° C., 190° C., and 180° C., and the screw speed is 200 rpm.
[0109] Example 5
[0110] An antibacterial TPV material for automobiles and a preparation method thereof, comprising the following components in parts by weight:
[0111] EPDM rubber: 100 parts;
[0112] Polypropylene: 60 parts;
[0113] Filler: carbon black:wollastonite = 1:2 composition, 40 parts;
[0114] Filler oil: paraffin oil, 80 parts;
[0115] Antimicrobial agent: 2 parts;
[0116] Curing agent: dicumyl peroxide DCP, 2 parts;
[0117] Vulcanizing agent: 1 part;
[0118] Antioxidant: 1 part;
[0119] Anti-ultraviolet agent: 2-hydroxy-4-methoxy-benzophenone, 1 part.
[0120] Among them, the antibacterial agent is the CS / ZnO / SiO2 composite material prepared in Example 1, the vulcanizing agent is triallyl cyanurate (TAC), and the antioxidant is antioxidant 1076.
[0121] The preparation process is as follows:
[0122] S1: adding EPDM rubber, polypropylene, filler, filling oil, antibacterial agent, antioxidant and anti-ultraviolet agent into a mixer and mixing them evenly, and then feeding them into a twin-screw extruder for extrusion granulation to obtain semi-finished particles;
[0123] S2: The semi-finished product particles are mixed evenly with the vulcanizing agent and the co-vulcanizing agent, and then sent to a twin-screw extruder for mixing and vulcanization, extruded, cooled and shaped to obtain the antibacterial TPV material for automobiles.
[0124] Wherein, in step S1, the operating temperatures of each zone of the twin-screw extruder are: 150°C, 160°C, 170°C, 175°C, 180°C, 180°C, 170°C, and the screw speed is 280 rpm;
[0125] In step S2, the operating temperatures of each zone of the twin-screw extruder are 160° C., 170° C., 180° C., 185° C., 190° C., 190° C., and 180° C., and the screw speed is 220 rpm.
[0126] Example 6
[0127] An antibacterial TPV material for automobiles and a preparation method thereof, comprising the following components in parts by weight:
[0128] EPDM rubber: 100 parts;
[0129] Polypropylene: 60 parts;
[0130] Filler: carbon black:wollastonite = 1:2 composition, 60 parts;
[0131] Filler oil: paraffin oil, 60 parts;
[0132] Antimicrobial agent: 3 parts;
[0133] Curing agent: dicumyl peroxide DCP, 3 parts;
[0134] Vulcanizing agent: 2 parts;
[0135] Antioxidant: 0.5 parts;
[0136] Anti-ultraviolet agent: 2-hydroxy-4-methoxy-benzophenone, 0.5 parts.
[0137] The antibacterial agent is the CS / ZnO / SiO2 composite material prepared in Example 1, the vulcanizing agent is triallyl isocyanurate (TAIC), and the antioxidant is a combination of antioxidant 1010 and antioxidant 1076, with a mass ratio of 1:1.
[0138] The preparation process is as follows:
[0139] S1: adding EPDM rubber, polypropylene, filler, filling oil, antibacterial agent, antioxidant and anti-ultraviolet agent into a mixer and mixing them evenly, and then feeding them into a twin-screw extruder for extrusion granulation to obtain semi-finished particles;
[0140] S2: The semi-finished product particles are mixed evenly with the vulcanizing agent and the co-vulcanizing agent, and then sent to a twin-screw extruder for mixing and vulcanization, extruded, cooled and shaped to obtain the antibacterial TPV material for automobiles.
[0141] Wherein, in step S1, the operating temperatures of each zone of the twin-screw extruder are: 150°C, 160°C, 170°C, 175°C, 180°C, 180°C, 170°C, and the screw speed is 270 rpm;
[0142] In step S2, the operating temperatures of each zone of the twin-screw extruder are 160° C., 170° C., 180° C., 185° C., 190° C., 190° C., and 180° C., and the screw speed is 230 rpm.
[0143] Example 7
[0144] An antibacterial TPV material for automobiles and a preparation method thereof, comprising the following components in parts by weight:
[0145] EPDM rubber: 100 parts;
[0146] Polypropylene: 50 parts;
[0147] Filler: carbon black:wollastonite = 1:2 composition, 40 parts;
[0148] Filler oil: paraffin oil, 60 parts;
[0149] Antimicrobial agent: 1 part;
[0150] Curing agent: dicumyl peroxide DCP, 4;
[0151] Vulcanizing agent: 2 parts;
[0152] Antioxidant: 1 part;
[0153] Anti-ultraviolet agent: 2-hydroxy-4-methoxy-benzophenone, 0.5 parts.
[0154] The antibacterial agent is the CS / ZnO / SiO2 composite material prepared in Example 1, the vulcanizing agent is triallyl cyanurate (TAC), and the antioxidant is antioxidant 264.
[0155] The preparation process is as follows:
[0156] S1: adding EPDM rubber, polypropylene, filler, filling oil, antibacterial agent, antioxidant and anti-ultraviolet agent into a mixer and mixing them evenly, and then feeding them into a twin-screw extruder for extrusion granulation to obtain semi-finished particles;
[0157] S2: The semi-finished product particles are mixed evenly with the vulcanizing agent and the co-vulcanizing agent, and then sent to a twin-screw extruder for mixing and vulcanization, extruded, cooled and shaped to obtain the antibacterial TPV material for automobiles.
[0158] Wherein, in step S1, the operating temperatures of each zone of the twin-screw extruder are: 150°C, 160°C, 170°C, 175°C, 180°C, 180°C, 170°C, and the screw speed is 290rpm;
[0159] In step S2, the operating temperatures of each zone of the twin-screw extruder are 160° C., 170° C., 180° C., 185° C., 190° C., 190° C., and 180° C., and the screw speed is 240 rpm.
[0160] Example 8
[0161] An antibacterial TPV material for automobiles and a preparation method thereof, comprising the following components in parts by weight:
[0162] EPDM rubber: 100 parts;
[0163] Polypropylene: 50 parts;
[0164] Filler: carbon black:wollastonite = 1:2 composition, 60 parts;
[0165] Filler oil: paraffin oil, 80 parts;
[0166] Antimicrobial agent: 3 parts;
[0167] Curing agent: dicumyl peroxide DCP, 2 parts;
[0168] Vulcanizing agent: 1 part;
[0169] Antioxidant: 0.5 parts;
[0170] Anti-ultraviolet agent: 2-hydroxy-4-methoxy-benzophenone, 1 part.
[0171] The antibacterial agent is the CS / ZnO / SiO2 composite material prepared in Example 1, the vulcanizing agent is a composition of triallyl cyanurate (TAC) and triallyl isocyanurate (TAIC), the mass ratio of which is 1:1, and the antioxidant is a composition of antioxidant 264 and antioxidant 1010, the mass ratio of which is 1:1.
[0172] The preparation process is as follows:
[0173] S1: adding EPDM rubber, polypropylene, filler, filling oil, antibacterial agent, antioxidant and anti-ultraviolet agent into a mixer and mixing them evenly, and then feeding them into a twin-screw extruder for extrusion granulation to obtain semi-finished particles;
[0174] S2: The semi-finished product particles are mixed evenly with the vulcanizing agent and the co-vulcanizing agent, and then sent to a twin-screw extruder for mixing and vulcanization, extruded, cooled and shaped to obtain the antibacterial TPV material for automobiles.
[0175] Wherein, in step S1, the operating temperatures of each zone of the twin-screw extruder are: 150°C, 160°C, 170°C, 175°C, 180°C, 180°C, 170°C, and the screw speed is 300rpm;
[0176] In step S2, the operating temperatures of each zone of the twin-screw extruder are 160° C., 170° C., 180° C., 185° C., 190° C., 190° C., and 180° C., and the screw speed is 210 rpm.
[0177] Comparative Example 1
[0178] The specific gravity of each component in Comparative Example 1 is the same as that in Example 2, except that the antibacterial agent used is nano ZnO. The preparation process of Comparative Example 1 is the same as that of Example 2.
[0179] Comparative Example 2
[0180] The specific gravity of each component in Comparative Example 2 is the same as that in Example 2, except that the antibacterial agent used is chitosan. The preparation process of Comparative Example 2 is the same as that in Example 2.
[0181] Comparative Example 3
[0182] The specific gravity of each component in Comparative Example 3 is the same as that in Example 2, except that no antibacterial agent is added. The preparation process of Comparative Example 3 is the same as that of Example 2.
[0183] Comparative Example 4
[0184] The specific gravity of each component in Comparative Example 4 is the same as that in Example 2, except that the filler used is carbon black. The preparation process of Comparative Example 4 is the same as that of Example 2.
[0185] Comparative Example 5
[0186] The specific gravity of each component in Comparative Example 5 is the same as that in Example 2, except that the filler used is wollastonite. The preparation process of Comparative Example 5 is the same as that of Example 2.
[0187] Test method:
[0188] The materials prepared in Examples 2-8 and Comparative Examples 1-5 were tested for performance, and the testing methods for various performances are as follows:
[0189] (1) Shore hardness test method: Tested in accordance with GB / T531.1-2008.
[0190] (2) Tensile strength determination method: Determined in accordance with GB / T528-2009.
[0191] (3) Elongation at break determination method: Determined in accordance with GB / T528-2009.
[0192] (4) Compression set determination method: Determined in accordance with GB / T7759.1-2015.
[0193] (5) Determination of antibacterial performance: Determined in accordance with QB / T2591-2003.
[0194] Test results:
[0195] Table 1 Performance test results of embodiments and comparative examples
[0196]
[0197] It can be seen from Table 1 that the TPV materials prepared in Examples 2-8 have excellent antibacterial properties, and the antibacterial rates against Escherichia coli and Staphylococcus aureus are >90%.
[0198] In contrast, in Comparative Examples 1-2, single use of nano ZnO or chitosan as an antibacterial agent has poor antibacterial effect due to agglomeration effect or poor heat resistance.
[0199] The TPV material prepared without adding an antibacterial agent in Comparative Example 3 does not have an antibacterial effect. From Comparative Examples 4-5, it can be seen that the mechanical properties of the TPV material prepared by using the carbon black-wollastonite composite filler as a filler are better than those of a single substance as a filler, and the carbon black-wollastonite composite has a synergistic effect in providing mechanical properties.
[0200] In summary, the present invention provides an antibacterial TPV material for automobiles and a preparation method thereof, and prepares an automobile TPV material with good mechanical properties and antibacterial properties, which can fully meet the use requirements in automobiles.
[0201] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. An antibacterial TPV material for automobiles, characterized in that: The composition includes the following components in parts by weight: EPDM rubber: 100 parts; Polypropylene: 50-70 parts; Filler: 40-60 parts; Filler oil: 60-80 parts; Antibacterial agent: 1 to 3 parts; Vulcanizing agent: 2-4 parts; Vulcanizing agent: 1-2 parts; Antioxidant: 0.5-1 part; Anti-ultraviolet agent: 0.5-1 part; Wherein, the antibacterial agent is a chitosan / nano zinc oxide / porous silicon oxide composite material; The filler is a composition of carbon black and wollastonite.
2. The antibacterial TPV material for automobiles according to claim 1, characterized in that: The preparation method of the chitosan / nano zinc oxide / porous silicon oxide composite material comprises: Weigh chitosan, add it to acetic acid aqueous solution to dissolve, then add zinc acetate dihydrate, stir and react at 70°C after dissolution, gradually add NaOH solution to adjust the pH of the reaction solution to 9-10 to promote ZnO precipitation, and continue to stir the reaction solution to ensure that nano ZnO particles are fully formed; The mixture was allowed to stand for precipitation, filtered, and repeatedly washed with ethanol and deionized water until no residual liquid was left, and dried to obtain a chitosan-modified nano zinc oxide CS / ZnO composite material; Weigh porous SiO2 and prepare it into a 5% SiO2 suspension with deionized water; The CS / ZnO composite material was added to the prepared SiO2 suspension, stirred, allowed to settle, filtered, washed, dried at 70°C for 12 hours, and then dried at 150°C for 2 hours to obtain a chitosan / nano zinc oxide / porous silica composite material.
3. The antibacterial TPV material for automobiles according to claim 2, characterized in that: The mass ratio of chitosan to zinc acetate dihydrate is 1:1, and the mass concentration of the acetic acid aqueous solution is 1%.
4. The antibacterial TPV material for automobiles according to claim 2 or 3, characterized in that: The mass ratio of chitosan to porous SiO2 is 44:6, and the pore size of the porous SiO2 is 30-50 nm.
5. The antibacterial TPV material for automobiles according to claim 1, characterized in that: The mass ratio of the carbon black to wollastonite is 1:
2.
6. The antibacterial TPV material for automobiles according to claim 1 or 5, characterized in that: The third monomer in the EPDM rubber is ethylidene norbornene, accounting for 4.0-6.0% and having a Mooney viscosity of 60-70; the polypropylene is homopolymer polypropylene, with a melt flow rate of 2.5-3.5 g / 10 min.
7. The antibacterial TPV material for automobiles according to claim 6, characterized in that: The vulcanizing agent is a peroxide vulcanizing agent, including dicumyl peroxide DCP; The co-vulcanizing agent is one or a combination of triallyl cyanurate TAC and triallyl isocyanurate TAIC; The filler oil is paraffin oil.
8. The antibacterial TPV material for automobiles according to claim 7, characterized in that: The antioxidant is a hindered phenol antioxidant, including one or more combinations of antioxidant 1076, antioxidant 264, and antioxidant 1010; The anti-ultraviolet agent is a dihydroxybenzophenone, including 2-hydroxy-4-methoxy-benzophenone.
9. The method for preparing the antibacterial TPV material for automobiles according to any one of claims 1 to 8, characterized in that: include, Add EPDM rubber, polypropylene, filler, filling oil, antibacterial agent, antioxidant and anti-ultraviolet agent into a mixer and mix them evenly, then send them into a twin-screw extruder for extrusion and granulation to obtain semi-finished particles; The obtained semi-finished product particles are mixed evenly with a vulcanizing agent and a vulcanizing co-agent, and sent to a twin-screw extruder for mixing and vulcanization, extruded, cooled and shaped to obtain an antibacterial TPV material for automobiles.
10. The preparation method according to claim 9, characterized in that: The twin-screw extruder for preparing the semi-finished particles has an operating temperature of 150-180°C and a screw speed of 250-300 rpm; The mixture is sent to a twin-screw extruder for mixing and vulcanization, wherein the operating temperature of the twin-screw extruder is 160-190° C. and the screw speed is 200-250 rpm.
Citation Information
Patent Citations
Dynamic vulcanization antibacterial TPV composite material and preparation method thereof
CN107245187A
Film for antibacterial packaging bag and preparation method thereof
CN111410785A
TPV sealing strip material with antibacterial function and preparation method thereof
CN111548569A
TPV (thermoplastic vulcanizate) material for vehicles as well as preparation method and application thereof
CN114316447A
Cited By
Degradable food packaging bag and preparation process thereof
CN121224270A